MODEL PEMBERANTASAN TINDAK PIDANA KORUPSI PADA PEMILU / PEMILUKADA - Maman Budiman (JURNAL LITIGASI (e-Journal), 2020)
The state election/election of the regional head should be run as what is mandated in Pancasila and after regulations. The Election Commission/Regional Commission of Election as the organizer should drafted a comprehensive operational procedure of election referring to the regulations. The aim is for all contestants to not commit any fraud during election such as corruption. The method of research used in this writing was juridical empirical that is a research on some of the state administrations running for the election/the head of region election who were indicated committing corruption during election/election of the head of region. The steps after was to make an inventory, study, and examination on the secondary data such as Law No. 20, 2001 on the amendment of Law No. 31, 2001 concerning The Eradication of Corruption; Law No. 8, 2010 on Money Laundering and Law No. 7, 2017 concerning Election. Factors causing the state administrations to commit corruption during election/election of the head of region are internal such as greed, lust, and external factor such as political system of the state and the third factor that is factor of interest. The eradication model of corruption to be imposed on the state administrations during the election/election of the head of region is by criminally processing those accussed to commit corruption during election/election of the regional head and to enforce maximum punishment to promote deterrent effect. Keywords: corruption, elections, honesty, integrity.